Balancing the scales in China's smart courts: driving case standardisation through AI. (3rd July 2021) - Greenhouse, Elinor
ABSTRACT: This paper positions the use of new technologies in China's smart courts as a continuation of the professionalisation of China's judiciary. This series of reforms is the backbone of China's rule of law society reforms, as set out in the 14th five-year plan, and has been adopted as a method to standardise judgements within a court system headed by elite justices, yet underpinned by a legacy of under-qualified judges with significant practical experience. While the smart court systems have demonstrated significant savings in terms of time and costs for litigants, smart courts are no panacea for betterment of rule of law. The quality of judicial big data, potential black box nature and bias of the algorithms used, coupled with the potential for over-reliance or under-reliance on the software, all present significant challenges to the safe and successful deployment of legal tech in China's smart courts. Reaching the lofty goals set out for its use requires a consistent and mindful approach to the betterment of both the technology itself and the training of those using it, so that pitfalls and faults in its employ can be both ameliorated and flagged by the users themselves: the judges.